2012
DOI: 10.30684/etj.30.3.11
|View full text |Cite
|
Sign up to set email alerts
|

LDPC Error Floor Improvement

Abstract: The error-correcting performance of low-density parity check (LDPC) codes, when decoded using practical iterative decoding algorithms, is known to be close to Shannon limits. In this paper we study the LDPC codes performance when varying code rate, constellation level and the maximum number of iteration, this paper shows better coding gain can be obtained at the cost of higher complexity or higher bit rate. For some cases, due to their inability to reach very low bit error rates (e.g., 10− 12 ) at low signal-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Focusing on the LDPC error floor, to improve coding gain arrives at the expense of increasing complication or bit rate, and it is demonstrated were [56] demonstrated that a combination system based on LDPC as an internal code and the Bose, Chaudhuri, and Hocquenghem codes (BCH) as an exterior may lower error limit.The effect of LDPC upon system performance across Additive White Gaussian Noise (AWGN) with Binary Phase Shift Keying (BPSK) and some random fading (Raleigh and Rician) channels has been examined by [57]. The results demonstrate that LDPC is capable of enhancing transceiver systems for many channel types.…”
Section: Related Workmentioning
confidence: 99%
“…Focusing on the LDPC error floor, to improve coding gain arrives at the expense of increasing complication or bit rate, and it is demonstrated were [56] demonstrated that a combination system based on LDPC as an internal code and the Bose, Chaudhuri, and Hocquenghem codes (BCH) as an exterior may lower error limit.The effect of LDPC upon system performance across Additive White Gaussian Noise (AWGN) with Binary Phase Shift Keying (BPSK) and some random fading (Raleigh and Rician) channels has been examined by [57]. The results demonstrate that LDPC is capable of enhancing transceiver systems for many channel types.…”
Section: Related Workmentioning
confidence: 99%